The impact of fasting plasma glucose variability on osteoporotic fractures - Liu, Ri; Gao, Lishu; Guo, Lu; Xu, Wenqi; Wu, Shouling; Tian, Dehu (Frontiers in Endocrinology, 2023)
Purpose To investigate the impact of FPG variability on osteoporotic fractures in the entire community population. Methods All participants were from the Kailuan Study. Participants completed three consecutive surveys from 2006–2007, 2008–2009, and 2010–2011. We excluded individuals with an osteoporotic fracture in or prior to the index year and those without complete FPG records at the first 3 examinations. All participants were followed from the date of the 3rd examination to the first occurrence of an endpoint event or December 31, 2021. According to the SD of FPG levels, the included subjects were divided into three groups. A Cox proportional hazards model was performed to further analyze the effect of different FPG-SD groups on the risk of osteoporotic fractures. Results Ultimately, the study population included 57295 participants. During a median follow-up time of 11.00 years, we documented 772 new osteoporotic fracture cases. When evaluating the FPG-SD level as a categorical variable, the HRs for osteoporotic fractures were 1.07 (95% CI: 0.89-1.29) for T2 and 1.32 (95% CI: 1.10–1.60) for T3 when compared with T1. We found that increased FPG variability was associated with a greater risk of osteoporotic fractures in people with diabetes than in those without diabetes (47% vs. 32%) Conclusion Increased FPG variability was an independent predictor of incident osteoporotic fracture, especially in individuals older than 50 years old, nonobese individuals, diabetes patients, and individuals with positive FPG-SD variability.